Stenting of Unprotected Left Main Coronary Artery Stenosis: Immediate out comes in NICVD our Initial Experience - Karmakar, Kajal Kumar; Jamaluddin, Mir; Khalil, Ibrahim; Rashid, Bazlur; Litu, Rakibul Islam; Kabir, Humayun; Chowdhury, AHK; Majumder, AAS; Shaha, Chandan Kumar; Khair, Abul; Hasan, Zahid; Kabir, Shahin (University Heart Journal, 2015)
This study aims to describe the initial experiences and immediate outcomes of percutaneous coronary intervention (PCI) in patients with significant left main coronary artery disease with normal LV function in National Institute of Cardiovascular Diseases (NICVD), Dhaka. Left main coronary artery disease is regarded as an absolute contraindication for coronary angioplasty. Recently several reports on protected or unprotected LMCA stenting or both suggested the possibility of percutaneous intervention for this prohibited area. The study was conducted in National Institute of Cardiovascular diseases & Hospital, Dhaka, Bangladesh. Participants of the study were 100 patients with a diagnosis of critical left main coronary artery disease. Information was collected on their demographic characteristics and clinical history. Relevant physical examination and laboratory investigation were performed. Percutaneous transluminal coronary angioplasty (PTCA) with stent implantation were done in the left main coronary artery and other culprit vessel where required. They were followed up thoroughly during the hospital stay. The study subjects were from 35 to 70 years old. 70 male and 30 female were included in this study. According to the clinical history, 12 lead surface ECG reading and cardiac enzyme analysis 40% patient was diagnosed as unstable angina, 40% presented with chronic stable angina and rest of them presented with old myocardial infarction. Among the study population critically isolated LM disease were 30%, critical left main with other vessels disease were 70%. The pattern of LM disease involvement were osteal 40%, mid shaft 10%, distal bifurcation 30%, entire LM involving bifurcation 20%. Procedural success rate was 100%. No patient faced major advance cardiac events (MACE) during hospital stay. Stenting of unprotected LM coronary artery stenosis may be safe effective alternative to CABG in carefully selected patients with normal LV function. Further studies in larger population of this group are needed to assess late out comes. University Heart Journal Vol. 10, No. 1, January 2014; 7-12